Rewriting Techniques and Applications 20th International Conference, RTA 2009 Brasl̕ia, Brazil, June 29 - July 1, 2009 Proceedings - Treinen, Ralf. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 20th International Conference on Rewriting Techniques and Applications, RTA 2009, held in Brasl̕ia, Brazil, during June 29 - July 1, 2009. The 22 revised full papers and four system descriptions presented were carefully reviewed and selected from 59 initial submissions. The papers cover current research on all aspects of rewriting including typical areas of interest such as applications, foundational issues, frameworks, implementations, and semantics.